Outcomes of Early versus Late Endotracheal Intubation in Patients with Initial Non-Shockable Rhythm Cardiopulmonary Arrest in the Emergency Department - Kiattichai Daorattanachai; Winchana Srivilaithon; Vitchapon Phakawan; Intanon Imsuwan (Emergency Medicine International)
Background. Sudden cardiac arrest is a critical condition in the emergency department (ED). Currently, there is no considerable evidence supporting the best time to complete advanced airway management (AAM) with endotracheal intubation in cardiac arrest patients presented with initial non-shockable cardiac rhythm. Objectives. To compare survival to hospital discharge and discharge with favorable neurological outcome between the ED cardiac arrest patients who have received AAM with endotracheal intubation within 2 minutes (early AAM group) and those over 2 minutes (late AAM group) after the start of chest compression in ED. Methods. We conducted a retrospective cohort study involving the ED cardiac arrest patients who presented with initial non-shockable rhythm in ED. Multivariable logistic regression analysis was used to evaluate the independent effect of early AAM on outcomes. The outcomes included the survival to hospital discharge and discharge with favorable neurological outcome. Results. There were 416 eligible participants: 209 in the early AAM group and 207 participants in the late AAM group. The early AAM group showed higher survival to hospital discharge compared with the late AAM group, but no statistically significant difference (adjusted odds ratio (aOR): 1.28, 95% confidence interval (CI): 0.59 -2.76, p=0.524). Discharge with favorable neurological outcome is also higher in the early AAM group (aOR: 1.68, 95% CI, 0.52 -5.45, p=0.387). Conclusion. This study did not demonstrate a significant improvement of survival to hospital discharge and discharge with favorable neurological outcome in the ED cardiac arrest patients with initial non-shockable cardiac arrest who underwent early AAM within two minutes. More research is needed on the timing of AAM and on airway management strategies to improve survival.